Neurobiological correlates of change in adaptive behavior in autism - Pretzsch, Charlotte M.; Schäfer, Tim; Lombardo, Michael V.; Warrier, Varun; Mann, Caroline; Bletsch, Anke; Chatham, Chris H.; Floris, Dorothea L.; Tillmann, Julian; Yousaf, Afsheen; Jones, Emily; Charman, Tony; et al. (The American journal of psychiatry, 2022)
Objective: - - Autism spectrum disorder (ASD) is a lifelong neurodevelopmental condition that is associated with significant difficulties in adaptive behavior and variation in clinical outcomes across the life span. Some individuals with ASD improve, whereas others may not change significantly, or regress. Hence, the development of “personalized medicine” approaches is essential. However, this requires an understanding of the biological processes underpinning differences in clinical outcome, at both the individual and subgroup levels, across the lifespan. - - Methods: - - The authors conducted a longitudinal follow-up study of 483 individuals (204 with ASD and 279 neurotypical individuals, ages 6-30 years), with assessment time points separated by ∼12-24 months. Data collected included behavioral data (Vineland Adaptive Behavior Scale-II), neuroanatomical data (structural MRI), and genetic data (DNA). Individuals with ASD were grouped into clinically meaningful “increasers,” “no-changers,” and “decreasers” in adaptive behavior. First, the authors compared neuroanatomy between outcome groups. Next, they examined whether deviations from the neurotypical neuroanatomical profile were associated with outcome at the individual level. Finally, they explored the observed neuroanatomical differences’ potential genetic underpinnings. - - Results: - - Outcome groups differed in neuroanatomical features (cortical volume and thickness, surface area), including in “social brain” regions previously implicated in ASD. Also, deviations of neuroanatomical features from the neurotypical profile predicted outcome at the individual level. Moreover, neuroanatomical differences were associated with genetic processes relevant to neuroanatomical phenotypes (e.g., synaptic development). - - Conclusions: - - This study demonstrates, for the first time, that variation in clinical (adaptive) outcome is associated with both group- and individual-level variation in anatomy of brain regions enriched for genes relevant to ASD. This may facilitate the move toward better targeted/precision medicine approaches.